2009
DOI: 10.1002/lt.21811
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation using controlled donation after cardiac death donors: An analysis of a large single-center experience

Abstract: The use of donation after cardiac death (DCD) donors may provide a valuable source of organs for liver transplantation. Concerns regarding primary nonfunction (PNF) and intrahepatic biliary stricture (IHBSs) have limited the enthusiasm for their use. A retrospective analysis of 1436 consecutive deceased donor liver transplants performed between December 1998 and October 2006 was conducted. These included 108 DCD liver transplants, which were compared to 1328 transplants performed with organs from donors meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(168 citation statements)
references
References 23 publications
7
159
1
1
Order By: Relevance
“…20 It has been shown by previous authors that DCD organs are used more frequently than DBD organs in patients with HCC (20.2% versus 13%). 4,21 The present study examined the effects of the use of DCD allografts in patients with HCC on patient and graft survival. Despite adherence to listing criteria such as the Milan criteria, 22 patients with HCC are known to have slightly inferior long-term survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It has been shown by previous authors that DCD organs are used more frequently than DBD organs in patients with HCC (20.2% versus 13%). 4,21 The present study examined the effects of the use of DCD allografts in patients with HCC on patient and graft survival. Despite adherence to listing criteria such as the Milan criteria, 22 patients with HCC are known to have slightly inferior long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that DCD livers are used more frequently than donation after brain death (DBD) organs in patients with HCC (20.2% versus 13%). 3,4 This may reflect the global tendency to transplant extended criteria organs into recipients with lower unadjusted Model for End-Stage Liver Disease (MELD) scores because of the perception that these patients are better equipped to weather the storm of an extended criteria organ; however, this view has been challenged. 5,6 DCD organs suffer from warm ischemic injury (which is not seen in traditional DBD organs) because of hypoperfusion and hypoxia during the agonal period.…”
mentioning
confidence: 99%
“…44,74 Once mechanical ventilation is re-initiated, tidal volumes should be 6-8 mgÁkg -1 with 8-10 cm H 2 O PEEP in order to decrease the risk of acute lung injury. 6 Liver transplantation Although favourable outcomes have been achieved with the use of DCD liver grafts, 75 there has been a higher rate of biliary complications associated with these organs, and thus, they are considered to represent a higher risk option for the recipient. Factors such as patient weight, total ischemia time, and donor age can affect recipient outcome.…”
Section: Lung Transplantationmentioning
confidence: 99%
“…To assess the outcomes of patients receiving DCD liver allografts, we analyzed the available previously published literature, including several single-center studies (Table 1) 6,[12][13][14][15][16][17][18][19] and large studies (Table 2) 7,[20][21][22][23][24][25] of national databases, to compare the outcomes of recipients who received DCD versus DBD donor livers and to better understand the risk factors for graft survival, loss, and failure.…”
Section: Current Practice and Outcome Of Donation After Cardiac Deathmentioning
confidence: 99%